Job Satisfaction and Turnover Intention among the Skilled Personnel in TRIplc Berhad - Masdia, Masri (2009)
This study examines the relationship between four factors of job satisfaction which is pay, promotion, the work itself and supervision, and turnover intention among skilled personnel at TRIplc Berhad. In addition, the study also attempts to determine the differences in the turnover intention based on demographic variables (age and tenure). The study also hypothesised that there are significant differences in the turnover intention of the skill personnel at TRIplc Berhad at different age and length of service;and there is a dominant factor influencing turnover intention among skilled personnel in the organisation. Three research instruments were used to obtain data: a questionnaire, interview and observation. A total of 120 respondents were randomly selected as the sample of study and data was analysed by “Statistical Package for Social Science” (SPSS Window) Version 12.0. The tests involved are ANOVA, Pearson Correlation Coefficient and Multiple Regression.The findings of the study show that majority of the respondents are 32 years old and above, Moreover, 48.3 percent of the respondents have been working with TRIplc Berhad for more than 7 years and above. The result of job satisfaction and turnover intention generally support the hypothesis. Supervision demonstrates the strongest relationship. However, the result shows neither age groups nor length of service groups have significant difference with turnover intention. These findings show that the related factors should have given attention to retain employees in the organisation. Some suggestions have been recommended for the organisation and for future research to be more complete and comprehensive.